2010
DOI: 10.1016/j.cellimm.2010.04.011
|View full text |Cite
|
Sign up to set email alerts
|

IgE regulates T helper cell differentiation through FcγRIII mediated dendritic cell cytokine modulation

Abstract: Asthma and allergy are characterized by dysregulation of inflammatory responses toward Th2 responses and high serum levels of IgE. IgE plays a role in the effector phase by triggering the degranulation of mast cells after antigen-cross-linking but its role in the induction of helper T cell differentiation is unknown. We have previously shown lymphotoxin is required for maintaining physiological levels of serum IgE which minimize spontaneous Th1-mediated airway inflammation, suggesting a physiological role for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…In addition, IgE can bind to other receptors, such as galectin-3 and FcγRIII. Whereas IgE-FcγRIII ligation on DCs has been shown in mice to promote Th2 responses through inhibition of IL-12 production [27], the role of these alternate receptors for IgE responses in human asthma remains unknown.…”
Section: Role Of Ige and Its Receptorsmentioning
confidence: 99%
“…In addition, IgE can bind to other receptors, such as galectin-3 and FcγRIII. Whereas IgE-FcγRIII ligation on DCs has been shown in mice to promote Th2 responses through inhibition of IL-12 production [27], the role of these alternate receptors for IgE responses in human asthma remains unknown.…”
Section: Role Of Ige and Its Receptorsmentioning
confidence: 99%
“…This “flood” of polyclonal IgE fosters the acquired immune response via dendritic cell FcεRI and Fcγ receptors and, consequently, a Th2 response [39]. …”
Section: The Intersection Of Two Pathsmentioning
confidence: 99%
“…It was shown previously that IgE stimulates DCs directly through Fc␥RIII to suppress IL-12 production in vitro and influences APCs to skew CD4 ϩ T cells toward Th2 differentiation. Blink and Fu [154] demonstrated recently a novel role for IgE in regulating differentiation of adaptive immune responses through direct interaction with Fc␥RIII on DCs. In a different study, pDCs from patients with asthma were shown to secrete significantly less type I IFN upon exposure to influenza A virus, and secretion was inversely correlated with serum IgE levels [155].…”
Section: Regulatory Mechanisms and Networkmentioning
confidence: 99%